(3EOGQI GdCYeGd (B:s (3EOGQI GdJaGhV (B/s - (3GdLGHQ, gGfjs ((3GdEScfOQjI(B: s (3ecJHI heWHYI GdETYGY GdafjI(B, s, 2006)
(3af GdJaGhV hGdcSH GdeJHGOd(B-(3CaUd GdfGS Yf GdeTcdI(B-(3cja JMUd Ydi (B"(3fYe(B"-(3cja JUHM eaGhVG fGLMG(B-(3eGPG jMOK Ef de jbhehG HGdJMQjc(B-(3GdfGS JSCd Yf cjajI GdhUhd Edi fYes
Keywords: (3EOGQI GdCYeGds